PRICING SYSTEM IN LAND LEASING IN REVIEW OF IJĀRAH 'ALA AL-MANĀFI' CONTRACT: A CASE STUDY IN ACEH BESAR - Munawarah, Rizka; Melayu, Hasnul Arifin; Fitria, Nurul (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
In the fiqh context of land leasing, there are variations in scholarly opinion regarding the legality and conditions of leasing. Some scholars argue that the leased land must provide direct benefits to the tenant, such as for agriculture, while others allow leasing for commercial activities. Rental pricing is a major concern as factors such as location, economic potential and land condition affect the rental value. This study aims to determine the system of determining land rental prices for business premises in the perspective of the ijarah 'ala al manafi' contract. Qualitative methods are used with observation and interview techniques to understand the practice of leasing in the perspective of Islamic economics. From this research, the results obtained in the practice of leasing land in Krueng Barona Jaya District, the principles of Islamic law, especially in the ijârah 'ala al-manâfi' contract, have generally been followed, including clarity of object, price, and time period. However, there is a discrepancy in terms of land benefits that cannot be obtained directly, which according to the view of the Shafi'iyah scholars, states that the benefits of the lease must be used immediately. Therefore, there needs to be more attention in ensuring the agreement is in accordance with the provisions of fiqh so that all parties get fair rights and obligations, and to achieve blessings in every transaction.